THE COMBINED EFFECT OF TBSV P19 MUTANTS AND HEAVY METALS ON ANTIOXIDANT ENZYME ACTIVITY: THE COMBINED EFFECT OF TBSV P19 MUTANTS AND HEAVY METALS ON ANTIOXIDANT ENZYME ACTIVITY - Akbassova, A.; Beisekova , M.; Tassanbiyeva , A.; Zhamshitova , D.; Kurmanbayeva, A.; Zhangazin , S.; Moldakimova , N.; Shalabayeva , A.; Masalimov , Zh.; Akbassova , A. (Eurasian Journal of Applied Biotechnology, 2023)
Crops of food value are often exposed to viral pathogens. Therefore, crops can noticeably decrease or die completely. For example, in 2021, the tomato brown wrinkle virus was detected in Kazakhstan, the main hosts of which are tomatoes and peppers. At the same time, in farms where the pathogen was detected, yield loss ranged from 30 to 70%. Therefore, it is important to develop methods aimed at increasing plant stress tolerance to viral infection. The scientific novelty of this manuscript is that previously the simultaneous effect of viral pathogens and heavy metals on plants has not been studied. Antioxidant enzymes play an important role in regulating the concentration of reactive oxygen species in plant cells. The enzyme catalase catalyzes the conversion of hydrogen peroxide into water and molecular oxygen, thereby neutralizing superoxide radicals. Thus, antioxidant enzymes prevent tissue damage and necrosis. Molybdenum enzymes can produce reactive oxygen species when exposed to adverse conditions, such as pathogen infestation or drought. Molybdenum is an integral part of the Moco cofactor within molybdoenzymes, but tungsten has the ability to substitute for molybdenum, resulting in a reversible loss of enzyme function. Consequently, tungsten acts as a stressor for plants. Inoculation of plants with tomato bush stunt virus of the wild type leads to their death. At the same time, when infected with TBSV 157, RMJ1 and RMJ2 mutants, the plants recovered after some time. Plants are expected to be more viable when the subject is exposed to heavy metal solutions and inoculated with viruses.